Maternal high fat diet exposure modifies amniotic fluid metabolites and expands group 3 innate lymphoid cells dependent on the maternal microbiome and MyD88-signaling - Niu, Xinying; Lu, Dongmei; Jaleel, Sana; Palmer, Suzette N.; Mahendroo, Mala; Zhan, Xiaowei; Mirpuri, Julie (Frontiers in Immunology, 2024)
BackgroundMaternal high fat diet (mHFD) exposure expands IL-17 producing group 3 innate lymphoid cells (IL17+ve ILC3) in the small intestine of neonatal murine offspring and increases their susceptibility to intestinal inflammation. How mHFD modulates innate immunity in the fetal offspring remains unclear.MethodsDams were exposed to 60% high fat diet or maintained on regular diet (RD) prior to and during mating. Amniotic fluid (AF) was collected during mid-pregnancy and metabolites examined by global non-targeted mass spectrometry in conventional wild-type (WT) and germ-free pregnant dams. Offspring were delivered by C-section or vaginally and fecal contents examined for major bacterial phyla and small intestinal lamina propria cells (LP) by flow cytometry. Susceptibility to intestinal inflammation was determined using a lipopolysaccharide and platelet-activating factor model (LPS/PAF) in WT, germ-free and MyD88 deficient offspring. Neonatal germ-free pups were exposed to HFD or RD AF by gavage and LP examined by flow cytometry.ResultsWe identified differentially produced metabolites in mHFD AF when compared to RD AF in conventionally raised mice, with no difference seen in germ-free mice. C-section delivery maintained the mHFD phenotype of expansion of IL17+ve ILC3 and increased susceptibility to inflammation in neonatal offspring. In addition, mHFD offspring had expansion of IL17+ve ILC3 at birth and 2 weeks of life, which was not seen in germ-free and MyD88 KO mice exposed to mHFD. Germ-free and MyD88 KO mice were protected from mHFD induced LPS/PAF injury and IL17+ve ILC3 expansion, demonstrating that the maternal microbiome and MyD88 are prenatally necessary for the expansion of IL17+ve ILC3 in mHFD offspring. Furthermore, introduction of mHFD AF to neonatal germ-free pups by gavage was sufficient to expand IL17+ve ILC3 in the small intestine.ConclusionOur findings indicate that mHFD interacts with the maternal microbiome to modify AF metabolites and signal via MyD88 to expand IL17+ve ILC3 in murine neonatal offspring.